2008
DOI: 10.1177/1934578x0800300111
|View full text |Cite
|
Sign up to set email alerts
|

A Pyranochalcone and Prenylflavanones from Tephrosia pulcherrima (Baker) Drumm

Abstract: A new 2',6'-dimethoxy-4',5'-(2",2"-dimethyl)-pyranochalcone (1) and three known flavanones, namely 5-hydroxy-7methoxy-8-(3,3-dimethylallyl)-flavanone (methyl glabranin) (2), 5,7-dimethoxy-8-(3,3-dimethylallyl)-flavanone (candinone) (3) and 5-O-methyl obovatin (pongachin) (4), have been isolated from the chloroform extract of the roots of Tephrosia pulcherrima. The flavonoids were fully characterized by detailed 1D-and 2D-NMR spectroscopic investigations. The pyranochalcone 1 showed significant antimicrobial ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…; Leguminosae) afforded the pyranochalcone 448, which showed antimicrobial activity against a panel of test organisms. 357 MeOH extracts of the leaves of breadfruit, Artocarpus communis J.R.Forst & G.Forst (a synonym of Artocarpus altilis (Parkinson ex F.A.Zorn) Fosberg; Moraceae), yielded 5 0geranylisoliquiritigenin (450) and a cyclised analogue, isolespeol (449), both of which showed cytotoxicity towards a panel of human cancer cell lines. 358 Isolespeol (449) was most active against human liposarcoma SW 872 cells (IC 50 ¼ 3.8 mM), in which it induces apoptosis through Fas-and mitochondria-mediated pathways.…”
Section: Chalconesmentioning
confidence: 99%
“…; Leguminosae) afforded the pyranochalcone 448, which showed antimicrobial activity against a panel of test organisms. 357 MeOH extracts of the leaves of breadfruit, Artocarpus communis J.R.Forst & G.Forst (a synonym of Artocarpus altilis (Parkinson ex F.A.Zorn) Fosberg; Moraceae), yielded 5 0geranylisoliquiritigenin (450) and a cyclised analogue, isolespeol (449), both of which showed cytotoxicity towards a panel of human cancer cell lines. 358 Isolespeol (449) was most active against human liposarcoma SW 872 cells (IC 50 ¼ 3.8 mM), in which it induces apoptosis through Fas-and mitochondria-mediated pathways.…”
Section: Chalconesmentioning
confidence: 99%
“…Several reports have indicated that extracts of some species of the genus have antibacterial, antifungal, insecticidal, antiviral, antiprotozoal, , antiplasmodial, antioxidant, and cytotoxic activities. Phytochemical investigations have revealed the presence of glycosides, rotenoids, isoflavones, chalcones, flavanones, flavanols, flavones, and prenylated flavonoids of chemotaxonomic importance in the genus . Flavonoids can act as phytoestrogens, as some bind to estrogen receptor (ER) subtypes and activate their signaling pathways. , In humans, two ER isoforms have been identified (ERα and ERβ), and physiological responses to estrogen are thought to be mediated through these two receptors.…”
mentioning
confidence: 99%
“…2',6'-Dimethoxy-4',5'-(2'',2''-dimethyl)-pyranochalcone ( 14 0 ) from T . pulcherrima showed significant antimicrobial activity when tested against a series of micro-organisms [7]. 3,4:8,9-Dimethylenedioxypterocarpan ( 13 1 ) from T .…”
Section: Biological Activitiesmentioning
confidence: 99%
“…The genus Tephrosia , belonging to the Leguminosae family, is a large pantropical genus of more than 350 species, many of which have important traditional uses [1,2]. Phytochemical investigations have revealed the presence of glucosides, rotenoids, isoflavones, chalcones, flavanones, flavanols, and prenylated flavonoids [1,2,3,4,5,6,7,8,9] of chemotaxonomic importance in the genus [10]. Moreover, bioactivity has been studied extensively, indicating that chemical constituents and extracts of the genus Tephrosia exhibited diverse bioactivities, such as insecticidal [11], antiviral [12], antiprotozoal [13], antiplasmodial [14] and cytotoxic [15] activities.…”
Section: Introductionmentioning
confidence: 99%